2015
DOI: 10.1039/c5ay00295h
|View full text |Cite
|
Sign up to set email alerts
|

Direct analysis in real time mass spectrometry of fused ring heterocyclic organometallic compounds

Abstract: Note demonstrates ability to gain analytical mass spectrometry data from organometallics without significant sample preparation or solubility issues for ionization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…DART mass spectrometry also confirms the molecular mass of oxiranes 1 – 5 , with the expected [M+1]+ ion peak observed for each case. This observance is typical for positive scan mode in DART . Elemental analysis was performed for all previously unreported compounds (oxazines 2 , 4 , and 5 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…DART mass spectrometry also confirms the molecular mass of oxiranes 1 – 5 , with the expected [M+1]+ ion peak observed for each case. This observance is typical for positive scan mode in DART . Elemental analysis was performed for all previously unreported compounds (oxazines 2 , 4 , and 5 ).…”
Section: Resultsmentioning
confidence: 97%
“…The mass spectrometry analysis was performed with a direct analysis in real‐time SVP ion source (IonSense, Saugus, MA, USA) interfaced with a LTQ XL linear ion trap mass spectrometer (Thermo Scientific, San Jose, CA, USA). Specific details for this system and operation have been previously reported . All data reported here are under Positive Scan mode.…”
Section: General Experimentalmentioning
confidence: 99%
“…Mazzotta et al also reported the analysis of fused ring heterocyclic organometallic compounds using DART. 20…”
Section: Direct Analysis In Real Timementioning
confidence: 99%
“…DART emitter nozzles are typically positioned between 8 and 15 mm from the entrances of mass spectrometers. [50][51][52] The sample vial that delivers analyte vapour to the DART source was kept in the same position for all experiments (,1 cm below the capillary entrance to the mass spectrometer). The temperature of the capillary entrance to the mass spectrometer was set to 1508C, which is the minimum temperature that enabled the detection of benzylammonium in reasonably high abundances under these conditions.…”
Section: Dart Source Distance and Temperaturementioning
confidence: 99%